Adsorption isotherm studies of Cd (II), Pb (II) and Zn (II) ions bioremediation from aqueous solution using unmodified and EDTA-modified maize cob - Igwe, Jude Chibuzo; Augustine, Augustina (Eclética Química, 2007)
The need to clean-up heavy metal contaminated environment can not be over emphasized. This paper describes the adsorption isotherm studies of Cd (II), Pb (II) and Zn (II) ions from aqueous solution using unmodified and EDTA-modified maize cob. Maize cob was found to be an excellent adsorbent for the removal of these metal ions. The amount of metal ions adsorbed increased as the ini- tial concentration increased. Also, EDTA - modification enhanced the adsorption capacity of maize cob probably due to the chelating ability of EDTA. Among the three adsorption isotherm tested, Dubinin- Radushkevich gave the best fit with R 2 value ranging from 0.9539 to 0.9973 and an average value of 0.9819. This is followed by Freundlich isotherm (Ave. 0.9783) and then the Langmuir isotherm (Ave. 0.7637). The sorption process was found to be a physiosorption process as seen from the apparent ener- gy of adsorption which ranged from 2.05KJto 4.56KJ. Therefore, this study demonstrates that maize cob which is an environmental pollutant could be used to adsorb heavy metals and achieve cleanliness thereby abating environmental nuisance caused by the maize cob.